Constelação sistêmica sub judice - Beserra, Danusa Regina Filgueira (Universidade Federal Rural do Semi-Árido, 2018)
The present work intends to present the Systemic Constellation as a differentiated conception of the right to solve emotional conflicts and humanize justice. A long time ago, jurisdiction was the only form of resolution. Faced with new social facts and new demands in the judiciary, it is possible to perceive that laws, doctrine and jurisprudence are not able to present a response, because they do not reach the core of the problem, nor do they solve the conflicts found in custody, alienation parental, affective abandonment and adoption. Systemic Law presents itself as a solution to the need for change. Authors such as Marinoni, Theodoro Júnior, Rocha, Almeida and Minister Andrigh of the STJ have warned of the importance of rethinking civil proceedings, while society receives the New Code of Civil Procedure, which lists consensual forms of conflict resolution. The Systemic Right values the Constellation, which is a psychotherapeutic technique, developed by the German philosopher and psychotherapist Bert Hellinger, implanted in the Brazilian courts through Dr. Sami Storth, magistrate of the Court of Justice of Bahia, that to resolve the conflicts in the Family Sticks and Childhood and Youth where you work. Storth sought this instrument of Psychology and thus began a pioneering work with the National Council of Justice. In the end, it is intended to conclude that this method is sufficient and able to resolve the dispute, lead social pacification and avoid new legal demands.
Artigo Acadêmico
Keywords: Constelação; Psicologia; Direito sistêmico; Justiça; Constellation; Psychology; Systemic law; Justice; CIENCIAS SOCIAIS APLICADAS::DIREITO